Heavy metal and soluble organic matter removal using natural conglomerate and siltstone soils: Towards soil aquifer treatment for oily wastewater - Ali, Jisha Kuttiani (2024)
The present work aims to assess the viability of vadose zone siltstone and conglomerate for oil and gas-produced water (PW) treatment using soil aquifer treatment (SAT). Comprehensive batch adsorption tests were carried out to analyze siltstone and conglomerate removal capacity for dissolved organics (phenol), and heavy metal ions (Ni 2+, and Zn 2+). The results demonstrated that conglomerate displayed a 98% removal capacity for Zn 2+ and 88% for Ni2+ while siltstone showed 82% removal for Zn2+ and 88% removal for Ni 2+. However, both siltstone and conglomerate showed low phenol removal (32% for siltstone, and 9% for conglomerate). The equilibrium adsorption isotherms were fitted by several adsorption models. The Langmuir model exhibited the best fitting for the adsorptions of phenol, Ni 2+ ions, and Zn 2+ ions on the two soils. The kinetics studies have revealed that phenol, Ni 2+ ions, and Zn 2+ ions adsorption on the two soil samples obey a pseudo-second-order kinetic model. Furthermore, Fourier transform infrared spectroscopy studies revealed that the Si-O peak in the soil plays a predominant role in interactions with heavy metal ions and phenol due to its high content in the soils. However, the electrostatic interactions between functional groups (Si-O, CO32-, and Cdouble bondO carbonyl groups) of the soil samples and the Ni2+ ions, Zn2+ ions, and phenol also contributed to the removal capacity. It is revealed that Zn2+ has a greater affinity for carboxyl groups than Ni2+. The obtained data in this study would support the effective design of SAT treatment for PW and help in reducing the risk of contaminating the groundwater aquifer.